The cynicism and Corporate Governance - Guarniz Izquierdo, Reynaldo Antonio (2017)
In this article, the author explains about the adoption of corporate governance practices, which depends on an evaluation of costs and benefits. Peruvian companies do not assume these practices because of the lack of incentives, informality and poor regulation. Finally, he concludes peruvian regulation of corporate governance practices lacks content, which means that it is not a priority for companies.